Determinan literasi digital mahasiswa: kasus Universitas Sriwijaya [Determinants of students digital literacy: the case of Sriwijaya University] - Mery Yanti (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2016)
Artikel ini bertujuan menganalisis kontribusi kesenjangan digital terhadap tingkat literasi digital di kalangan mahasiswa Universitas Sriwijaya. Peneliti menggunakan pendekatan kuantitatif. Populasi penelitian adalah seluruh mahasiswa FISIP Universitas Sriwijaya yang berjumlah 3.414 orang. Sampel penelitian ditetapkan secara purposif sebanyak 200 orang dan dipilih dengan metode simple random sampling. Seratus responden dipilih dari kelompok digital native di Kampus Palembang dan 100 orang lagi dipilih dari Kampus Indralaya. Data dikumpulkan dengan wawancara terstruktur berpedoman pada kuesioner yang telah disiapkan. Data dianalisis dengan SPSS dan menggunakan tabulasi silang (chi-square dan uji Somers). Hasilnya, kesenjangan digital di kalangan mahasiswa Universitas Sriwijaya berbentuk perbedaan kepemilikan, biaya komunikasi, dan usia pertama kali mengoperasikan perangkat TIK (laptop, tablet, dan handphone). Hampir tidak ada perbedaan dalam tiga situs website yang paling sering dikunjungi, tiga tempat favorit mengakses internet, intensitas penggunaan, dan pola pemanfaatan perangkat TIK. Tingkat literasi digital mahasiswa FISIP Universitas Sriwijaya adalah ‘Tinggi’ dan ‘Sangat tinggi’. Ia tidak berhubungan dengan jenis kelamin, program studi, kepemilikan dan intensitas penggunaan TIK, keanggotaan dalam grup online, dan biaya komunikasi yang dikeluarkan. Secara statistik, literasi digital dipengaruhi usia pertama kali menggunakan perangkat TIK. Tetapi hubungan keduanya bersifat negatif dan tidak signifikan.*****This article aims to analyze the contribution of the digital divide to digital literacy among students in Sriwijaya University (SU), by using quantitative approach. Research population was 3,414 students at Faculty of Social and Political Sciences, SU. Research sample consists of 200 students chosen purposively by using simple random sampling method. A hundred students were selected from digital native in Palembang Campus, while the other 100 were from Indralaya Campus. Data were collected by a structured interview based on questionnaire and were analyzed using SPSS and cross tabulation (chi-square and Somers test). The results show that the digital divide among students in SU occurs in the forms of differences of ICT devices ownership, communication costs, and the age when the respondent used ICT devices (laptops, tablets, and mobile phones) for the first time. There is no difference between respondents in the aspects of three most frequently-visited websites, three favorite places in accessing the Internet, and the intensity and usage pattern of ICT devices. We also found that the digital literacy of SU students are in the level of 'high' and 'very high'. However, it does not relate to gender, discipline, ownership and usage intensity of ICT devices, membership in online groups, and communication costs. Statistically, digital literacy is influenced by the age when a respondent used an ICT device for the first time. In contrast, this relationship is negative and insignificant.